1995
DOI: 10.1159/000276716
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid as a Molecular Filter and Friction-Reducing Lubricant in the Human Inner Ear

Abstract: Immunofiuorescence for hyaluronic acid occurred intracellularly in morphologically highly specialized areas in the adult human inner ear, for instance in the cuticular plates of all types of hair cells, at the apposition between outer hair cells and Deiter’s cell bodies and in the near-surface area of Hensen’s cells. The cytoskeletal organization in these regions is characterized by tightly packed filamentous proteins. Under physiological stimulus these regions undergo micromechanical change, either actively m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In most tissue types, HA is cellularly internalized via HA-specific receptor mediated processes (Misra et al, 2015). The main HA receptor responsible for internalization is Cluster of Differentiation 44 (CD44); however, currently there are very limited data available on the presence of CD44 or endogenous HA in cochlear structures (Vilstrup and Jensen, 1954;Friberg et al, 1989;Anniko and Arnold, 1995;Hertzano et al, 2010). A survey of the gEAR multi-omic database (Orvis et al, 2021) indicated that CD44 is expressed in murine cochlear structures at the mRNA level (Hertzano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In most tissue types, HA is cellularly internalized via HA-specific receptor mediated processes (Misra et al, 2015). The main HA receptor responsible for internalization is Cluster of Differentiation 44 (CD44); however, currently there are very limited data available on the presence of CD44 or endogenous HA in cochlear structures (Vilstrup and Jensen, 1954;Friberg et al, 1989;Anniko and Arnold, 1995;Hertzano et al, 2010). A survey of the gEAR multi-omic database (Orvis et al, 2021) indicated that CD44 is expressed in murine cochlear structures at the mRNA level (Hertzano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a concomitant alteration in the basal cells was associated with the accumulation of matrix in age-related morphological change [41]. Hyaluronic acid is distributed as a tissue-specific manner and, predominantly, in the spiral ligament of the inner ear [42,43]. Bianchetti et al [44] demonstrated that fibrocytes synthesized and released proteoglycan and exerted in a positive dominance for hyaluronic acid synthase-2 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of hyaluronic acid in the middle ear is well established. Animal studies have shown that transtympanic application does not cause hair cell death or measurable decline in hearing thresholds (Anniko & Arnold, 1995;Anniko, Hellstrom, & Laurent, 1987;Bjurstrom, Slepecky, & Angelborg, 1987;Engstrom, Bjurstrom, Jansson, Engstrom, & Angelborg, 1987;Martini et al, 1992). In contrast, intracochlear injection of hyaluronic acid resulted in permanent sensorineural hearing loss in rats (Roland, Magardino, Go, & Hillman, 1995).…”
Section: Application Of Healon® To the Cochleostomy And Electrode Arraymentioning
confidence: 99%